A study on correlation of serum IgE levels with diagnosis and severity of asthma in children - G., Snehalatha; Begum, Ayesha; N., Raju; N., Ravi Kumar (International Journal of Contemporary Pediatrics, 2018)
Background: Asthma is a chronic inflammatory airway disorder which increases bronchial hyperreactivity to various allergens and irritants characterized by narrowing of airways. Immunoglobulin E (Ig E) plays major role in the pathogenesis of asthma which is produced due to dysregulation of type 2 T helper lymphocytes (Th2) induced cytokines in genetically susceptible individual after exposing to allergens or irritants. The aim of this study was to estimate serum Ig E level in children between 3-12 years of age and to correlate it with the clinical diagnosis and severity of asthma. Methods: A prospective interventional study was done over a period of one year, enrolling 81 children aged between 3-12 years, who were newly diagnosed cases of asthma attending asthma clinic in a tertiary care pediatric government hospital. Serum IgE level was estimated and its correlation with the severity of asthma was assessed. Results: The mean Absolute Eosinophil Count (AEC) of the study was 305.85±188.40 cells /mm3. Mean Ig E level was increased in asthmatic children (874.59±287 IU/ml). Mean serum Ig E level in mild intermittent asthma was 247.92 ± 89.50 IU/ml, in mild persistent asthma was 742.95±306.78 IU/ml, in moderate persistent asthma was 1142±196.88 IU/ml and in severe persistent asthma was 1790±121.50 IU/ml. The increasing level of serum Ig E was found to be statistically significant (p <0.05) with increasing grading of asthma. Conclusions: Elevated serum IgE levels support clinical diagnosis of asthma in children and can predict severity of asthma and can be used to counsel parents for better compliance in the management of bronchial asthma.